The heterogenous course of drug transit through the body - Dokoumetzidis, A.; Karalis, V.; IIiadis, A; Macheras, P. (TRENDS IN PHARMACOLOGICAL SCIENCES, 2004)
Advances in mathematics and physics that deal with fractal geometry, fractal kinetics and chaotic dynamics have offered new insights for complex, kinetic and dynamical phenomena. These concepts can be applied to describe the heterogeneous nature of drug processes in the human body. Using these concepts, all processes related to gastrointestinal drug absorption (i.e. dissolution or release, transit and uptake) are considered to take place in non-homogeneous, disordered media. In pharmacokinetic modeling, fractal spaces and branching transport networks, or stochastic models, replace the classical compartmental models. Classical pharmacodynamics relies on the suppression or amplification of a steady-state baseline; however, the underlying physiological systems are often much more complex. Therefore, tools of nonlinear dynamics are used to analyze the drug effect.